Prevalence of anabolic steroid users seeking support from physicians: a systematic review and meta-analysis - Andreas Kimergård; Paolo Deluca; Julio Mario Xerfan Amaral (BMJ Open)
Objectives To estimate the overall prevalence of androgenic-anabolic steroids (AAS) users seeking support from physicians. Secondary objectives are to compare this prevalence in different locations and among subpopulations of AAS users, and to discuss some of the factors that could have influenced the engagement of AAS users with physicians.Design Systematic review and meta-analysis.Data sources MEDLINE, PsycINFO, Web of Science and SciELO were searched in January 2022.Eligibility criteria Quantitative and qualitative studies reporting the number of AAS users who sought support from physicians, with no restrictions of language or time of publication.Data extraction and synthesis Two independent reviewers extracted data and assessed the quality of studies, including publication bias. A random-effects meta-analysis was performed to estimate the overall prevalence of AAS users seeking support from physicians, followed by pooled prevalence rates by studies’ location and the subpopulation of AAS users.Results We identified 36 studies published between 1988 and 2021, involving 10 101 AAS users. The estimated overall prevalence of AAS users seeking support from physicians is 37.12% (95% CI 29.71% to 44.52%). Higher prevalence rates were observed in studies from Australia (67.27%; 95% CI 42.29% to 87.25%) and among clients of the needle and syringe exchange programme (54.13%; 95% CI 36.41% to 71.84%). The lowest prevalence was observed among adolescent AAS users (17.27%; 95% CI 4.80% to 29.74%).Conclusion Our findings suggest that about one-third of AAS users seek support from physicians, with remarkable differences between locations and subpopulations of AAS users. Further studies should investigate the factors influencing the engagement of AAS users with physicians.PROSPERO registration number CRD42020177919.